Human cerebral organoids: Complex, versatile, and human-relevant models of neural development and brain diseases - Raquel Coronel; Rosa González-Sastre; Patricia Mateos-Martínez; Laura Maeso; Elena Llorente-Beneyto; Sabela Martín-Benito; Viviana S. Costa Gagosian; Leonardo Foti; Ma Carmen González-Caballero; Victoria López-Alonso; Isabel Liste (Neural Regeneration Research)
The brain is the most complex human organ, and commonly used models, such as two-dimensional-cell cultures and animal brains, often lack the sophistication needed to accurately use in research. In this context, human cerebral organoids have emerged as valuable tools offering a more complex, versatile, and human-relevant system than traditional animal models, which are often unable to replicate the intricate architecture and functionality of the human brain. Since human cerebral organoids are a state-of-the-art model for the study of neurodevelopment and different pathologies affecting the brain, this field is currently under constant development, and work in this area is abundant. In this review, we give a complete overview of human cerebral organoids technology, starting from the different types of protocols that exist to generate different human cerebral organoids. We continue with the use of brain organoids for the study of brain pathologies, highlighting neurodevelopmental, psychiatric, neurodegenerative, brain tumor, and infectious diseases. Because of the potential value of human cerebral organoids, we describe their use in transplantation, drug screening, and toxicology assays. We also discuss the technologies available to study cell diversity and physiological characteristics of organoids. Finally, we summarize the limitations that currently exist in the field, such as the development of vasculature and microglia, and highlight some of the novel approaches being pursued through bioengineering.